METHYLATION RELATED TO BENEFIT AND HARM IN RNAI APPLICATION: AN EPIGENETIC QUASI SYSTEMATIC REVIEW - Peni Kistijani Samsuria; Indranila Kustarini Samsuria (Sekolah Ilmu Kesehatan Dan Ilmu Alam (SIKIA), Universitas Airlangga, 2020)
Background: Double stranded RNA (dsRNA), siRNA, miRNA, RNAi, induce DNA methylation in plants and in mammalian cells, including human. Methylation of CpG island and repeat CGG DNA is high prevalence cases in tropical rain forest, but had been neglected till now. Purpose: Aims are knowing the effect of gene silencing to the environment, whereas RNAi cause hypermethylation. Methods: The manuscript was Quasi Systematic Review with Bayesian Analysis. Results: The result used Science Direct search engine, 935 references are caught, plus 11 references from already recorded in Mendeley library and after screening the abstract or title, 920 are excluded with the not relevant either duplication analyzed with the newest Bayesian network to answer the hypothesis. Screening full text of the 18, plus 10 references from already recorded in Mendeley library, then 16 full text were chosen. The chasing 28 full text were check and recheck with meta-analysis of RNAi-methylation using Science Direct (12 references). Conclusion: All of the studies described above indicated that RNAi and CRISPR/Cas9- mediated editing in plant, fishery, mammals, human, based on methylation and demethylation technique set-up by siRNA, miRNA or CRISPR/Cas9.